Digitalization in The Public Sector During A Pandemic - Shotarov, Antoan (Research Papers, 2024)
The COVID-19 pandemic caused significant negative changes in all areas - economic, social, humanitarian, etc. The pandemic does not have the same impact – strength and direction (positive/negative influence) towards all areas. There are even areas that the pandemic have had a stimulating effect. The aim of the study is to analyze the impact of the pandemic on digitalization in the public sector and to derive the main characteristics of this impact. This article presents some of the scientific results of the research project "Digital Public Sector" (NID 21-2020, UNWE).